Радиационное дефектообразование в кристаллах KCl - Нуритдинов, И; Муссаева, М.А; Юлдашов, Д.П; Аташов, Б.Т (SCIENCE and SOCIETY, 2026)
This work presents the results of studying radiation-induced defect formation in KCl crystals exposed to X-ray and gamma irradiation. It is shown that F-centers begin to form from the early stages of irradiation and reach saturation at doses of about 100 rad. At higher doses (Dγ ≥ 10⁵ rad), absorption bands corresponding to I- and V-centers appear, indicating the formation of new structural defects. The mechanisms of creation and stabilization of these defects are analyzed.
Keywords: potassium chloride (KCl); X-ray irradiation; absorption spectra; color centers